2023
DOI: 10.3390/su15075636
|View full text |Cite
|
Sign up to set email alerts
|

Green Human Resource Management: Mapping the Research Trends for Sustainable and Agile Human Resources in SMEs

Abstract: While individual SMEs may have a minor environmental footprint, their collective influence is characterized as significant. Through the dynamics of their employees, green human resource management can help SMEs reduce their environmental footprint. However, SMEs face difficulties in implementing such strategies and achieving sustainable business continuity. The current research aims to propose the theoretical framework of a business model that will help SMEs adjust to the new environment, address their sustain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“…Some scholars have pointed out that green human resource management can motivate employees to behave green. It is a new business model that helps enterprises realize green organizational citizenship behaviors and promotes enterprises to improve their sustainable development capabilities [51].…”
Section: Esg and Green Innovationmentioning
confidence: 99%
“…Some scholars have pointed out that green human resource management can motivate employees to behave green. It is a new business model that helps enterprises realize green organizational citizenship behaviors and promotes enterprises to improve their sustainable development capabilities [51].…”
Section: Esg and Green Innovationmentioning
confidence: 99%
“…The direct impact of PEB contributes to reducing energy and raw material consumption, pollution and waste. The indirect impacts can be in the form of identifying environmental damage to ecological facilities and equipment, as well as modification practices in business (Papademetriou et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Many experts and researchers have found that green job analysis, green hiring, green performance evaluation, green training, and green awards significantly improve a company's green performance. These experts believe that eco-friendly initiatives and environmental management practices cannot be implemented adequately without GHRM (Papademetriou et al, 2023). GHRM highlights the importance of human resource management in environmental prevention, control and protection in business operations.…”
Section: Introductionmentioning
confidence: 99%
“…*Job satisfaction is a major imperative factor influencing human resource efficiency and efficiency (Dhir and Chakraborty, 2023). The most valuable resource in any organization is its human resources, which drive long-term service delivery (Kumar et al, 2013;Papademetriou et al, 2023). India is facing a serious shortfall in human health resources.…”
Section: Introductionmentioning
confidence: 99%